PERILAKU PEMBELIAN MEREK FAST FASHION PADA GENERASI MILENIAL DI INDONESIA - Enrico Situmorang; Boginskaya Letsoin; Arton Briyan; Liya Suryani; Ayu Ekasari; Kurniawati (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The purpose of this study is to analyze millennial buying behavior towards world fast fashion brands in Indonesia. The total number of respondents in the research that could be processed was 188 respondents. The criteria for respondents are the millennial generation in Indonesia who bought Zara, H&M and Uniqlo brand products. The data analysis of this study used LISREL 8.80. The results of this study have a positive effect on brand awareness and store atmosphere and the hypothesis is supported on millennials' purchasing behavior; brand nationality and brand consciousness have a negative effect and the hypothesis is not supported on millennials' purchasing behavior; brand consciousness and brand nationality have a positive influence and the hypothesis is supported on brand awareness; brand awareness has a mediating role and the hypothesis is supported between brand consciousness and brand nationality on millennials' purchasing behavior; Brand schematicity does not have a moderating role and the hypothesis is not supported by brand awareness, brand consciousness and brand nationality on millennials' purchasing behavior. The implication of this research is that fast fashion brands can increase brand awareness and store atmosphere to maximize the potential opportunities for fast fashion brands to millennials' purchasing behavior. Keywords: brand awareness, brand consciousness, brand nationality, brand schematicity, store atmosphere